Impact of extending direct antiviral agents (DAA) availability in France: an observational cohort study (2015-2019) of data from French administrative healthcare databases (SNDS). - Stanislas Pol; Fayssoil Fouad; Magali Lemaitre; Ingrid Rodriguez; Olivier Lada; Pascaline Rabiega; Elias Benabadji; Françoise Roudot-Thoraval (Elsevier, 2022)
Summary: Background: Direct antiviral agents (DAAs) became available in France in 2014 for the treatment of chronic hepatitis C (CHC) in patients with severe fibrosis (prioritized access); in 2017, DAAs became available to all CHC patients (universal access). We evaluated the impact of extending DAA availability on CHC patient care, especially on screening and time to treatment. Methods: Adult patients affiliated with the national health insurance system (SNDS) who were screened or treated for CHC between 2015 and 2019 were included. Algorithms were developed to identify at-risk subpopulations. Findings: The proportion of screened patients increased by 1% between 2015 and 2019, from 4·6% to 5·6%. The main nonexclusive risk factors for CHC were psychiatric conditions (27%), drug use (21%) and HIV positivity (11%); more than 50% of psychiatric patients had additional risk factors, mainly drug use with a 38% to 52% overlap.The median interval between the last screening test and treatment initiation decreased from 64 days in 2015 to 37 days in 2019.During the study period, 71,466 patients began CHC treatment (median age 55 [48-62]; 59% male), including 46% of "at-risk" patients with an increase in treatment initiation by 44% between 2015 and 2017 and a decrease of 46% between 2017 and 2019. Only 2,212 (3%) patients were treated at least twice.Among treated patients, the proportion of HIV+ patients decreased from 19% to 8% (prioritization consequence), while the proportions increased in the other at-risk subpopulations. Interpretation: we showed that policies extending DAA availability are associated with a screening increase and a decrease in the time to treatment initiation, while universal access led to a surge in treatment initiations in 2017. This study may also contribute to improving the cascade of care in the at-risk subpopulations. For instance, by pointing out their relative importance, especially for the psychiatric subpopulation, it highlights the importance to address them with tailored policies. Funding: This study was funded by Gilead Sciences.